Ethnic Identity and Work - Amelie F. Constant (Institute for the Study of Labor (IZA), 2014)
Immigrants do not fare as well as natives in economic terms; even after including many controls, an unexplained part remains. The ethnic identity entered the field of labor and migration economics in an effort to better explain the economic outcomes of immigrants, their behavior and their often perceived as irrational and suboptimal choices. Quantifying ethnic identity is a major issue; even more challenging is to measure its impact on economic outcomes such as the probability to work or the earnings of immigrants. The thin but burgeoning theoretical and empirical literature shows that ethnic identity has a significant impact on the economic behavior of immigrants.
Keywords: F22; J15; Z10; 330; assimilation; discrimination; employment; ethnic identity; ethnicity; human capital; identity; immigration; informal networks; labor force participation; labor markets; integration; marginalization; national identity; oppositional identity; separation; wages; work